2020
DOI: 10.1039/d0ra00623h
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive turn-off fluorescent detection of cyanide in aqueous medium using dicyanovinyl-substituted phenanthridine fluorophore

Abstract: Herein, the turn-off fluorescence sensor of 2-((4′-(7,8,13,14-tetrahydrodibenzo[a,i]phenanthridin-5-yl)-[1,1′-biphenyl]-4-yl)methylene)malanonitrile (7) was developed for the recognition of CN− ions and studied using different spectroscopic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Furthermore, the geometries of probe 1 and 1 :CN – obtained at the B3LYP/6-31G* level were subjected to TD-DFT studies using the B3LYP/6-31G* level for charge-transfer excitations. TD-DFT results were analyzed by employing Gauss-Sum 2.2.5 program, TD-DFT results obtained are reported in Table S1, it shows LUMO density toward cyanide, which is already discussed in the literature . From the TD-DFT results, it is seen that probe 1 (Figure S5) has absorption with high intensity compared with 1 :CN – (Figure S6).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, the geometries of probe 1 and 1 :CN – obtained at the B3LYP/6-31G* level were subjected to TD-DFT studies using the B3LYP/6-31G* level for charge-transfer excitations. TD-DFT results were analyzed by employing Gauss-Sum 2.2.5 program, TD-DFT results obtained are reported in Table S1, it shows LUMO density toward cyanide, which is already discussed in the literature . From the TD-DFT results, it is seen that probe 1 (Figure S5) has absorption with high intensity compared with 1 :CN – (Figure S6).…”
Section: Resultsmentioning
confidence: 79%
“…TD-DFT results were analyzed by employing Gauss-Sum 2.2.5 program, 49 TD-DFT results obtained are reported in Table S1, it shows LUMO density toward cyanide, which is already discussed in the literature. 56 From the TD-DFT results, it is seen that probe 1 (Figure S5) has absorption with high intensity compared with 1:CN − (Figure S6). Calculation of the HOMO and LUMO from CV is shown in Table S3.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The absorption spectrum of probe 53 shows three bands, an intense at 375 nm and two lower intensity bands at 270 nm and 298 nm, evidencing ICT processes due to its high π-conjugation. 79 This probe also was evaluated by cyclic voltammetry, proving that the addition of CN − causes the reduction potential of 53 at −1.41 eV to shift towards more negative potentials, reaching up to −1.07 eV for the adduct 53-CN. These results show that the sensing mechanism involves a shutdown by the ICT process from the N-heterocyclic core to the dicyanovinylidene moiety in 53.…”
Section: Chemosensors For Cn − Sensingmentioning
confidence: 99%
“…In this case, Manickam and Iyer 79 developed probe 53 for sensing CN − , having tetrahydrodibenzo[ a , i ]phenanthridine. This probe showed a color change from yellow to colorless with the addition of CN − in acetonitrile according to sensing strategy I ( Fig.…”
Section: Chemosensors For Cn − Sensingmentioning
confidence: 99%
“…Iyer et al reported that a malononitrile-derived chemosensor, probe 61 , undergoes selective turn-off fluorescence recognition of CN − . 94 61 displayed a promising colorimetric response from orange to colourless in the presence of CN − upon irradiation with 365 nm light. The free 61 displayed immense fluorescence emission at around 594 nm upon photoexcitation at 370 nm.…”
Section: Chromo-fluorogenic Probes For the Detection Of Cn−mentioning
confidence: 99%